Komunikasi Organisasi SPBUN PTPN IV Sosa Dalam Meningkatkan Kinerja Karyawan - Atah Sulhansyah; Fadhil Pahlevi Hidayat (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2023)
Organizational communication is the process of creating and exchanging messages in a network of interdependent relationships to cope with uncertain or ever-changing environments. The purpose of this study is to find out "SPBUN PTPN IV Sosa Organizational Communication in Improving Employee Performance". The research method used is qualitative research, which is a form of research that aims to provide an overview of various field data collected objectively. Data collection techniques used are observation, interviews with a number of informants and documentation. For data analysis using a subjective qualitative approach using narrative research methods, where this data analysis uses interview and observation methods in the form of answering questions such as what, how or why and the data received from this method in the form of text or narrative. The results of this study can be seen that the communication carried out by the leaders of SPBUN PTPN IV Sosa is very good where they routinely hold daily and quarterly meetings to listen to the aspirations and ideas conveyed by members for the company. During this tenure there are no barriers in communication between leadership and employees, there is only difficulty gathering the entire employee.